2011
DOI: 10.1021/jp111175e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Dynamics of Histamine Monocation in Aqueous Solution: Car–Parrinello Molecular Dynamics and Vibrational Spectroscopy Study

Abstract: Hydration of histamine was examined by infrared spectroscopy and Car-Parrinello molecular dynamics simulation. Histamine is a neurotransmitter and inflammation mediator, which at physiological pH conditions is present mainly in monocationic form. Our focus was on the part of vibrational spectra that corresponds to histamine N-H stretching, since these degrees of freedom are essential for its interactions with either water molecules or transporters and receptors. Assignment of the experimental spectra revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 99 publications
3
50
0
Order By: Relevance
“…[108][109][110][111][112] Following discovery of water molecules durably located and proximate to sulfur, we began extensive CP-MD simulations to investigate the organization of water molecules around dissolved cysteine. 113 Preliminary low-temperature in silico experiments have produced H-bonding networks that include stabilized water molecules positionally compatible with the MXAN fit.…”
Section: Discussionmentioning
confidence: 99%
“…[108][109][110][111][112] Following discovery of water molecules durably located and proximate to sulfur, we began extensive CP-MD simulations to investigate the organization of water molecules around dissolved cysteine. 113 Preliminary low-temperature in silico experiments have produced H-bonding networks that include stabilized water molecules positionally compatible with the MXAN fit.…”
Section: Discussionmentioning
confidence: 99%
“…Vibrational spectroscopy techniques such as infrared spectroscopy have been applied to study the hydration of small molecules [68]. Hydrogen bonding studies using simulation and vibrational spectroscopy between membrane lipids and the protein [69,70] and also the lipid headgroups with water [71,72] showed that lipids not only provide a hydrophobic environment for membrane protein folding but also form hydrogen bonds with protein residues, which stabilize it within the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The approach involved the construction of one dimensional proton potentials on snapshot structures extracted from a CPMD trajectory, followed by solving the one-dimensional vibrational Schroedinger equation. By separating the amino N-H vibrations of the protonated ethylamino chain from those within the imidazole ring in the experimental spectra, we clearly demonstrated that the former moiety forms stronger hydrogen bonds with the surrounding water molecules, 9,10 which should be significant for the biological function of histamine. It remains a challenge to identify how the fluctuating intra-and intermolecular geometric parameters influence the N-H stretching frequencies, which is the aim of the present work.…”
Section: Introductionmentioning
confidence: 91%
“…The latter is in line with recent molecular dynamics simulations by Keserű and co-workers 7 that emphasized the role of water-histamine interactions at the binding site of the human histamine H4 receptor, being in agreement with several previous reports. 8 Recently, we modeled the nature of the hydration of physiological histamine monocation by using CarParrinello molecular dynamics simulations (CPMD) 9 and a static cluster model. 10 In the former study, we simulated the N-H stretching band envelope, which are degrees of freedom that predominantly influence the strength of the hydrogen bonding as probed by the vibrational spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation